Erica Montgomery: capstone - Montgomery, Erica, artist (Colorado State University. Libraries, 2026)
The artist's statement: My work centers on thoughtful, community-driven design that blends storytelling, strategy, and a sense of curiosity. I enjoy creating work that feels approachable, intentional, and rooted in real connection, whether through branding, illustration, photography, or tactile processes that shape my creative thinking. Collaboration is a major part of my process, and working with me means working with someone who values listening, flexibility, clear communication, and building ideas together from concept to completion. I'm inspired by culture, place, and the overlooked details that make people feel seen, and I aim to create designs that not only function well but leave a lasting impression people can genuinely connect with.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design